2020
DOI: 10.1016/j.jcmgh.2020.01.014
|View full text |Cite
|
Sign up to set email alerts
|

NCoR1 Protects Mice From Dextran Sodium Sulfate–Induced Colitis by Guarding Colonic Crypt Cells From Luminal Insult

Abstract: Intestinal epithelial cell-specific nuclear receptor corepressor 1 (NCoR1)-deficient mice show increased susceptibility to chemical-induced ulcerative colitis. Colonic stem cell proliferation and secretory cell differentiation are regulated by NCoR1. Disruption of NCoR1 weakened barrier protection, allowing luminal products such as butyrate to penetrate and synergistically damage colonic crypt cells.BACKGROUND & AIMS: Colonic stem cells are essential for producing the mucosal lining, which in turn protects ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Colonic stem cells are responsible for mucosal regeneration and the maintenance of stable colonic luminal environment, while the inner mucosa in turn protects colonic stem cells from damage by luminal contents. 41 Cldn-7 contributes to the maintenance of colonic epithelial integrity, whether there is a certain regulatory effect on colonic stem cells is unknown. In the next stage, we will explore the molecular mechanisms of how Cldn-7 and ISCs microenvironment influence the development and progression of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic stem cells are responsible for mucosal regeneration and the maintenance of stable colonic luminal environment, while the inner mucosa in turn protects colonic stem cells from damage by luminal contents. 41 Cldn-7 contributes to the maintenance of colonic epithelial integrity, whether there is a certain regulatory effect on colonic stem cells is unknown. In the next stage, we will explore the molecular mechanisms of how Cldn-7 and ISCs microenvironment influence the development and progression of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…As we all known from the previous research, IEC apoptosis or cell death induced by DSS contributed to disruption of intestinal integrity [ 30 , 33 ]. The cleaved caspase-3 and PCNA results in IHC analysis showed that DSS induced the apoptosis and suppressed the proliferation of intestinal epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…IEC maturation stems from deep intestinal crypt cells proliferating and differentiating into the absorptive and secretory cell lineages that constitute the intestinal villi (Yeung et al, 2011;De Mey and Freund, 2013). The maturation process is tightly controlled through transcriptional repressive actions which include NCoR1, and if these repressive states are interrupted or released, accelerated proliferation and differentiation occurs (Mottis et al, 2013;Jo et al, 2015;Mennillo et al, 2020). We have currently established that the oral treatment of neonatal hUGT1 mice with isothiocyanates induces hepatic UGT1A1 through a CAR dependent mechanism that is directly linked to the development of hepatic oxidative stress (Yoda et al, 2017).…”
Section: Discussionmentioning
confidence: 99%